Contenido clorofílico del epifiton sobre Scirpus californicus en la laguna La Rosita (partido de Castelli) - Santos, Analía dos (2008)
La Rosita shallow lake is located in the south of Castelli city. With a surface area of 162 ha, 80% of the lake is covered by stands of californian bulrush. With the aim of studying dynamics of periphyton growth on this substrate, epiphytic chlorophyll content was analyzed in stands of Scirpus californicus located in shallow and deep zones, presenting differential development of floating and submerged macrophytes. Replicated samples of epiphyton were obtained monthly, during an annual period, by scrapping the total submerged area of bulrush axes in three sites of the shallow lake. Axe density was quantified in random fields and floating and submerged macrophyte cover percentages were estimated. Pigment extraction was performed according to Lorenzen (1967) and calculation of chlorophyll a concentration was carried out following Varela (1981). At the same time, water physic and chemical variables were measured. Evident spatial and temporal differences were found regarding epiphyton dynamics at the sampling points. At shallow sites (average depth 0,67 m), the maximum value of chlorophyll a concentration was 6,5 mg/m2, while at deep points (average depth 1,02 m) this variable only attained a maxima of 0,38 mg/m2. The factors that may have affected the chlorophyll content of periphyton were water column depth, submerged macrophyte cover (mainly Ceratophyllum demersum) and the age and growth period of californian bulrush. Floating macrophyte cover (principally Ricciocarpus sp.) may have affected too, no sufficient evidence could be gathered.